Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

answer for both boxes please :)​

Answer For Both Boxes Please class=

Sagot :

Answer:

(0, - 3 )

Step-by-step explanation:

Given the 2 equations

6x - 4y = 12 → (1)

- 6x + y = - 3 → (2)

Add (1) and (2) term by term to eliminate x, that is

0 - 3y = 9

- 3y = 9 ( divide both sides by - 3 )

y = - 3

Substitute y = - 3 into either of the 2 equations and solve for y

Substituting into (1)

6x - 4(- 3) = 12

6x + 12 = 12 ( subtract 12 from both sides )

6x = 0 , thus

x = 0

solution is (0, - 3 )

We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.